Reduction of Gibbs free energy and enhancement of Methanosaeta by bicarbonate to promote anaerobic syntrophic butyrate oxidation. (November 2018) - Zhang, Yupeng; Li, Jianzheng; Liu, Fengqin; Yan, Han; Li, Jiuling; Zhang, Xue
Graphical abstract: Pathway of methanogenesis of butyrate. Highlights: Novel function of HCO3 − in anaerobic digestion were revealed. Δ G of syntrophic butyrate methanogenesis could be decreased by additional HCO3 − . Proton transfer among syntrophic consortia was enhanced by additional HCO3 − . Additional HCO3 − enhanced Methanosaeta abundance but decreased acetate degradation. Methanogenesis of butyrate was enhanced by additional HCO3 − as a result. Abstract: Bicarbonate (HCO3 − ) has been extensively researched as a buffer in anaerobic digestion. The effect of HCO3 − concentration on syntrophic butyrate oxidation process was evaluated by batch culturing of anaerobic activated sludge, and the mechanism was further revealed by the changes of Gibbs free energy (Δ G ) and the interspecies transfers of electron and proton. The results showed that butyrate degradation rate was enhanced by 32.07% when the supplement of HCO3 − increased from 0 to 0.20 mol/L. However, methane production and acetate degradation were strongly inhibited by HCO3 − more than 0.10 mol/L. More function of HCO3 − was found as 1) decreasing the Δ G of syntrophic methanogenesis of butyrate while increasing the Δ G of methanogenesis of acetate, 2) enriching M. harundinacea and M. concilii, 3) increasing the diffusion rate of protons between the syntrophic consortia. This work would increase the anaerobic digestion efficiency by enhancing the interaction of the syntrophic consortia.